By introducing heterogeneous interfaces: Improved fatigue crack growth resistance of a metastable β titanium alloy. (November 2022) - Li, Tianle; Wu, Huiping; An, Dayong; Chen, Jieshi; Li, Xifeng; Chen, Jun
Abstract: We present a method for the improvement of the fatigue crack growth (FCG) resistance of a metastable β titanium alloy with uncompromised high strength and ductility by introducing more heterogeneous interfaces produced by diffusion bonding. FCG behavior and tensile properties of this bonded alloy were measured at room temperature. The detailed features of α grains precipitated at the laminated interface and substate during furnace cooling and subsequent aging treatment were characterized. Dense α grains, grain boundary α (αWG ) layer-free, and residual stress due to compression strain at the laminated interface can hinder FCG, resulting in an increase of FCG life of 9.4% in the high-layers laminated structure (HLS) sample compared with the low-layers laminated structure (LLS) sample. This available method can be also extended to other near and metastable β titanium alloys as a reference for designing enhanced FCG resistance with uncompromised tensile performance. Graphical abstract: Image, graphical abstract